Aligned carbon nanotube based sensors for strain sensing applications - Santos, Ana Raquel Ribeiro (2019)
This paper presents an aligned carbon nanotube (CNT)-based strain sensor. Vertical aligned carbon nanotubes (VA-CNT), synthesized by chemical vapour deposition (CVD), were knocked down onto polymeric films, in order to obtain a thin 10 × 10 × 0.05 mm CNT patch. Different polymeric substrates, ADEXepoxy, polyethylene terephthalate (PET) and polyimide (PI) were used. The samples’ morphology before and after the knock down process, specifically their alignment, was observed by scanning electron microscopy (SEM). The good quality of the synthesized VA-CNT was assessed by Raman spectroscopy. Furthermore, transmission electron microscopy (TEM) analysis was carried out to determine the average wall number and diameters (inner and outer) of the VA-CNT. A MATLAB software with an adapted Van der Pauw method for anisotropic conductors was developed to determine the electric properties of the obtained samples, which were strained in the transverse (X) and parallel (Y) directions with respect to the CNT alignment. The electric anisotropy, defined as electric resistance ratio between obtained measurements along the X (Rxx) and Y (Ryy) -axes, decreases with deformation increment when the sample was strained in the Y-direction, while it increases when strained in the X-direction. Moreover, the obtained Gauge factor values showed a much sensitive response to deformation, i.e., approximately 47% increase in GF values, when the samples are strained transversely to CNT alignment. These results showed that the piezoresistive CNT/polymeric based sensor produced is suitable for strain sensing applications.